2022
DOI: 10.3390/polym14225037
|View full text |Cite
|
Sign up to set email alerts
|

APTES-Modified Nanocellulose as the Formaldehyde Scavenger for UF Adhesive-Bonded Particleboard and Strawboard

Abstract: This work examines the possibility of applying non-modified nanocellulose and nanocellulose functionalized with 3-aminopropyltriethoxysilane (APTES) as a formaldehyde scavenger for commonly used urea-formaldehyde (UF) adhesive. The effect of silanization was determined with the use of Fourier transform infrared spectroscopy (FTIR), flame atomic absorption spectrometry (FAAS), and elemental analysis. Moreover, the ability of cellulosic nanoparticles to absorb the formaldehyde from an aqueous solution was invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 84 publications
1
6
0
Order By: Relevance
“…Additionally, peaks corresponding to Si-O-Si at 462.39, 802.76, and 1015 cm À1 and NH's bending and stretching vibrational modes at 1637 cm À1 and 3400 cm À1 were identified. [39][40][41] Notably, characteristic peaks at 1554 cm À1 for the CH-CH of benzene also confirmed that the MSN-PHS was obtained. 42 The weight loss of MSN was 11.0%, which increased to 27.5% after trimming PHS-APTES to MSN.…”
Section: Synthesis and Characterization Of Msn-phssupporting
confidence: 66%
“…Additionally, peaks corresponding to Si-O-Si at 462.39, 802.76, and 1015 cm À1 and NH's bending and stretching vibrational modes at 1637 cm À1 and 3400 cm À1 were identified. [39][40][41] Notably, characteristic peaks at 1554 cm À1 for the CH-CH of benzene also confirmed that the MSN-PHS was obtained. 42 The weight loss of MSN was 11.0%, which increased to 27.5% after trimming PHS-APTES to MSN.…”
Section: Synthesis and Characterization Of Msn-phssupporting
confidence: 66%
“…The mixture was stirred for 30 min and then the ground husk particles were soaked in the solution in a 1:5 mass ratio. The pH of the solution was decreased to 4 with acetic acid to increase the silanization effectiveness [32]. The reaction was run at room temperature for 3 h while stirring at 400 rpm.…”
Section: Buckwheat Husk Preparation and Modificationmentioning
confidence: 99%
“…(Tohmura et al 2001;Park and Jeong 2011b;Zaidon et al 2015;Antov et al 2020;Kristak et al 2022). It is still an aim for UF resins to develop such additives that lessen harmful emissions without degrading the mechanical and physical properties of wood-based composites (Kawalerczyk et al 2022).…”
Section: Introductionmentioning
confidence: 99%